Triptycene-terminated thiolate and selenolate monolayers on Au(111) - Liu, Jinxuan; Kind, Martin; Schüpbach, Björn; Käfer, Daniel; Winkler, Stefanie; Zhang, Wenhua; Terfort, Andreas; Wöll, Christof (Beilstein Journal of Nanotechnology, 2017)
To study the implications of highly space-demanding organic moieties on the properties of self-assembled monolayers (SAMs), triptycyl thiolates and selenolates with and without methylene spacers on Au(111) surfaces were comprehensively studied using ultra-high vacuum infrared reflection absorption spectroscopy, X-ray photoelectron spectroscopy, near-edge X-ray absorption fine structure spectroscopy and thermal desorption spectroscopy. Due to packing effects, the molecules in all monolayers are substantially tilted. In the presence of a methylene spacer the tilt is slightly less pronounced. The selenolate monolayers exhibit smaller defect densities and therefore are more densely packed than their thiolate analogues. The Se–Au binding energy in the investigated SAMs was found to be higher than the S–Au binding energy.
Keywords: organic thin films; selenolates; self-assembled monolayers; thiolates; triptycene